2018
DOI: 10.1097/pec.0000000000001615
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Chest Radiographs in Children Presenting to a Pediatric Emergency Department With Acute Asthma Exacerbation and Chest Pain

Abstract: Objectives: Previous studies have not evaluated the utility of obtaining chest radiographs (CXR) in patients with acute asthma exacerbation reporting chest pain. The aims of this study were to evaluate the symptom of chest pain as a predictor for clinicians obtaining a CXR in these patients and to evaluate chest pain as a predictor of a positive CXR finding.Methods: This was a retrospective chart review of patients, ages 2 to 18 years, presenting for acute asthma exacerbation to the emergency department from A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…29 Moreover, chest radiography was performed for patients with acute asthma exacerbations having fever, oxygen saturation of ≤92% in room air, younger age group (≤4 years of age), and for those who complain chest pain. 30,31 Certainly, physicians must confirm the diagnosis of pneumonia, pneumothorax, or pneumomediastinum to assist decision-making for treating acute asthmatic patients presented with such positive findings.…”
Section: Discussionmentioning
confidence: 99%
“…29 Moreover, chest radiography was performed for patients with acute asthma exacerbations having fever, oxygen saturation of ≤92% in room air, younger age group (≤4 years of age), and for those who complain chest pain. 30,31 Certainly, physicians must confirm the diagnosis of pneumonia, pneumothorax, or pneumomediastinum to assist decision-making for treating acute asthmatic patients presented with such positive findings.…”
Section: Discussionmentioning
confidence: 99%
“…The high accuracy of LUS for PNX in our study can have practical implications. Pediatric studies have shown the high rate of CXRs performed by emergency pediatricians evaluating children with acute chest pain ( 30 , 31 ). Considering the ability of LUS in detecting PNX, the high negative predictive value for PNX, and the available data on the accuracy of LUS in detecting PNX, the routine application of LUS can allow a high reduction of CXR-related costs and radiation exposure for the evaluation of acute chest pain in the pED.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary system-related chest pain is also not highly prevalent, accounting for 1.82–12.78% [ 1 , 9 , 12 , 14 , 15 , 16 , 17 , 31 ], with common causes including pneumothorax, asthma, pneumonia, and the less common pneumomediastinum [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Some of these diseases can be potentially life-threatening, such as tension pneumothorax.…”
Section: Etiology Of Chest Pain In Children and Adolescentsmentioning
confidence: 99%
“…Chest radiography is also a common examination for children and adolescents with acute chest pain. In previous studies, 35.6–72.0% of pediatric patients with chest pain underwent chest radiography [ 1 , 9 , 12 , 13 , 33 ]. Common positive findings on chest radiography included pneumonia/bronchitis, pneumomediastinum, pneumothorax, pneumopericardium, and cardiomegaly.…”
Section: Common Examinations Performed For Pediatric Chest Pain In Th...mentioning
confidence: 99%